(untitled) (Physical Education, Health and Social Sciences, 2026)
Antimicrobial resistance (AMR) has emerged as one of the most pressing global health threats of the 21st century, with bacterial AMR directly responsible for 1.27 million deaths and associated with nearly 5 million fatalities in 2019 alone. This review provides a comprehensive analysis of current resistance patterns among clinical pathogens, with particular emphasis on the ESKAPE group (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp.), which dominate healthcare-associated and community-acquired infections worldwide. Drawing on data from the WHO GLASS surveillance system and recent regional studies, the analysis reveals alarmingly high rates of multidrug resistance (MDR), extensively drug-resistant (XDR), and difficult-to-treat resistance (DTR) phenotypes, particularly to β-lactams, carbapenems, and fluoroquinolones. Gram-negative pathogens exhibit the most concerning trends, with carbapenem-resistant Klebsiella pneumoniae and Acinetobacter baumannii reaching 55–100% resistance in many settings. South Asia, including Pakistan, stands out as a major hotspot for XDR Salmonella Typhi and high rates of ESBL- and carbapenemase-producing Enterobacterales. The review elucidates key molecular mechanisms (enzymatic inactivation, target modification, efflux pumps, reduced permeability, and biofilm formation) and underscores the critical role of the One Health interface in resistance dissemination. Public health implications include increased mortality, prolonged hospital stays, higher treatment costs, and threats to modern medicine (surgery, chemotherapy, transplantation). Effective containment requires strengthened antimicrobial stewardship, rapid diagnostics, enhanced surveillance, and accelerated development of novel therapeutics. Without urgent, coordinated global action, AMR will continue to undermine healthcare systems and sustainable development goals.